Catálogos de Sciencias Juridicas e Sociaes em Pernambuco, Brasil - Whitaker Verri, Gilda Maria (2021)
The creation of the Course on Legal Sciences and Societies in Olinda, Pernambuco, required the formation of a library from acquired collections. The main objective of the work is to understand and demonstrate the scope and characteristics of the ordering of old books in the process of forming the original collection of the Legal Course, disseminated through handwritten lists, inventories and catalogs, which constitute and represent the period library itself. Through the eyes of the historical bibliography, information science and the epistemological approach, the cataloging process of his works was analyzed, for the constitution of the library that was established with the compilation of his catalogs.